Critical analysis of public service expenditure policies toward General Allocation Funds (GAF) for regional development in 2020 / Ayuni Nur Siami and Sulikah Asmorowati - Siami, Ayuni Nur; Asmorowati, Sulikah (2021)
Increase in spending on public services for the needs of people in the regions during the Covid-19 pandemic, led to an increase in the budget for public service functions. As a result of the covid-19 outbreak, the increase in spending on public services became 218.2%. The year 2020 is a time when economic instability occurs, so that it has an impact on budget changes that can be made at any time. This happens because people's needs are increasing, but income is decreasing. To overcome this condition, the government must set a strategy in conducting financial budgeting. Maximizing the GAF can be a solution to maintaining economic stability in the regions. Through the budgeting framed by the MTEF, public service spending in regions that use GAF has certainly about the allocation of funds in the medium term. It aims to analyze regional public service spending policies in Indonesia in 2020 which focus on regional development sub-functions, The main study of this paper is about the General Allocation Fund as a balance fund from the center, which was very influential during the Covid-19 pandemic. The type of research used is descriptive with qualitative data for content analysis and to study the information contained in writing documents or other communication media. The findings in this study reveal that GAF has an important role in helping economic stability in the regions, especially in developing. However, spending on public services in several regions sourced from the GAF is still ineffective and has not been on target because government agencies in several regions have not implemented the MTEF principles properly and even did not apply them at all.